Evaluation of treatment of patients with radicular pain in the lumbosacral part of the spine after periradicular, epidural steroid injection - Fiałkowski, Tomasz; Bujok, Jan; Szurmik, Tomasz Henryk; Majerski, Piotr (Journal of Education, Health and Sport, 2017)
Objective: The report presents an evaluation of treatment of patients with radicular pain in the lumbosacral part of the spine, who underwent the procedure of periradicular, epidural steroid injection. Method: Examination was performed in a group of 33 patients, 12 men and 21 women, with average age of 52 years and age range of 39-61 years. The patients were diagnosed with radicular syndrome and treated in Neurosurgical Unit of the Voivodeship Hospital in Bielsko-Biała, in the years 2015-2016. Examination program included assessment of pain scale and symmetry of standing position, and functional tests — Laseque and fingertip-to-floor test. Examination was conducted twice, before and after the procedure. Results: Administered therapy led to a significant improvement of the condition of the locomotor system, in terms of reduced pain, increased mobility of lower extremities and improved spine functions measured by means of Laseque test and fingertip-to-floor test. Conclusions: 1. Injection procedure significantly improves the measured parameters 2. Gender does not determine effectiveness of the procedure 3. Age does not determine the obtained results